2018
DOI: 10.1001/jamaophthalmol.2018.0026
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Multicolor Imaging in Patients With Asteroid Hyalosis

Abstract: Asteroid hyalosis is a degenerative change of the vitreous that consists of yellow-white opacities that reflect light and impede the quality of color fundus photography (CFP). 1 Eyes that have retinal disease along with dense asteroid hyalosis usually need spectral-domain optical coherence tomography (SD-OCT) or fluorescein angiography (FA) for adequate assessment of the retina. 2,3 Although SD-OCT and FA do provide information about anatomy of retinal layers and retinal blood vessels, they do not provide info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…OR CI 95% Weight Moss et al (2001) 2.20 1.66-2.93 38.8% Mitchell et al (2003) 2.54 1.25-5.16 14.2% Fawzi et al (2005) 1.40 0.98-1.99 32.8% Kim et al (2008) 1.32 0.65-2.68 14.2% Overall 1.80 1.32-2.45 100% Cochran's Q 5.4 I 2 , CI 95% 44.9 0.0-81.6 that enable fundus examination without artificial pupil dilation, such as scanning laser ophthalmoscopy and optical coherence tomography, may suffer from vitreous opacities (Browning & Fraser 2004;Hwang et al 2006;Alasil et al 2014;Saurabh et al 2018). Findings of Alasil et al (2014) suggest, however, that the faster technique of swept-source OCT may have advantages in this regard over spectral-domain optical coherence tomography in eyes with asteroid hyalosis.…”
Section: Referencesmentioning
confidence: 99%
“…OR CI 95% Weight Moss et al (2001) 2.20 1.66-2.93 38.8% Mitchell et al (2003) 2.54 1.25-5.16 14.2% Fawzi et al (2005) 1.40 0.98-1.99 32.8% Kim et al (2008) 1.32 0.65-2.68 14.2% Overall 1.80 1.32-2.45 100% Cochran's Q 5.4 I 2 , CI 95% 44.9 0.0-81.6 that enable fundus examination without artificial pupil dilation, such as scanning laser ophthalmoscopy and optical coherence tomography, may suffer from vitreous opacities (Browning & Fraser 2004;Hwang et al 2006;Alasil et al 2014;Saurabh et al 2018). Findings of Alasil et al (2014) suggest, however, that the faster technique of swept-source OCT may have advantages in this regard over spectral-domain optical coherence tomography in eyes with asteroid hyalosis.…”
Section: Referencesmentioning
confidence: 99%
“…CFP may also be limited when the view is restricted by coexisting media opacities such as cataracts or vitreous hemorrhage [21]. Some of these limitations are circumvented by MCI, which can be performed nearly simultaneously with SD-OCT, is less affected by media opacities due to suppression of light scatter, and can enable better resolution by eye tracking [22].…”
Section: Discussionmentioning
confidence: 99%
“…For fundus photographs or retinal angiography, better results may be obtained using scanning laser ophthalmoscopy-based systems, such as OPTOS (Figure 3). [29][30][31] Optical coherence tomography (OCT) often yields successful visualization of the retinal layers and the artifact from the asteroid bodies does not induce significant impact on the readability of the scans, 32,33 and it has been reported that swept-source based systems may be superior to spectral-domain based systems. 34 Further, it has been reported that optical coherence tomography angiography including widefield systems can successfully penetrate through the asteroid bodies and visualize neovascularizations, microaneurysms, and capillary dropout zones.…”
Section: Retinal Examinationmentioning
confidence: 99%